PERANCANGAN BUKU FOTOGRAFI NAMA –NAMA ALAT TRASPORTASI DENGAN SISTEM ISYARAT BAHASA INDONESIA (SIBI) SEBAGAI MEDIA PEMBELAJARAN SISWA TUNARUNGU DI TKLB-B KARYA MULIA SURABAYA - Caesario, Disna Wahyu; Riyanto, Darwin Yuwono; cinantya, ixsora gempita (Jurnal Art Nouveau, 2017)
for the Development of Transportation Terms with Bahasa Indonesia Sign Language System Photography Book as Learning Tools for kids with Hearing Impairment in TKLB-B Karya Mulia Surabaya.Today, education has been developed rapidly. However, there are still kids with disabilities. Hence, they need better understanding from special designed book for hearing impaired kids in the learing process.This particual book has to be developed using Bahasa Indonesia Sign Language System methods so that the kids would be motivated in studying and can achieve their dreams. Keywords: Ilustration, Design, SIBI, Transportation